Diagnosis and Management of Rare Cardiomyopathies in Adult and Paediatric Patients. A Position Paper of the Italian Society of Cardiology (SIC) and Italian Society of Paediatric Cardiology (SICP). (15th June 2022) - Limongelli, Giuseppe; Adorisio, Rachele; Baggio, Chiara; Bauce, Barbara; Biagini, Elena; Castelletti, Silvia; Favilli, Silvia; Imazio, Massimo; Lioncino, Michele; Merlo, Marco; Monda, Emanuele; Olivotto, Iacopo; et al.
Abstract: Cardiomyopathies (CMPs) are myocardial diseases in which the heart muscle is structurally and functionally abnormal in the absence of coronary artery disease, hypertension, valvular disease and congenital heart disease sufficient to cause the observed myocardial abnormality. Thought for a long time to be rare diseases, it is now clear that most of the CMPs can be easily observed in clinical practice. However, there is a group of specific heart muscle diseases that are rare in nature whose clinical/echocardiographic phenotypes resemble those of the four classical morphological subgroups of hypertrophic, dilated, restrictive, arrhythmogenic CMPs. These rare CMPs, often but not solely diagnosed in infants and paediatric patients, should be more properly labelled as specific CMPs. Emerging consensus exists that these conditions require tailored investigation and management. Indeed, an appropriate understanding of these conditions is mandatory for early treatment and counselling. At present, however, the multisystemic and heterogeneous presentation of these entities is a challenge for clinicians, and time delay in diagnosis is a significant concern. The aim of this paper is to define practical recommendations for diagnosis and management of the rare CMPs in paediatric or adult age. A modified Delphi method was adopted to grade the recommendations proposed by each member of the writing committee. Graphical abstract: The inherited and rare cardiomyopathy team. The multidisciplinary team, with specific expertise in inherited and rare CMPs, has the potential to improve diagnostic work-up and explore the available treatment options. The expertise required involves adult and paediatric cardiologists, genetic counsellors, electrophysiologists, geneticists, psychologists, intensive care specialists, cardiac surgeons and electrophysiologists Unlabelled Image Highlights: Rare cardiomyopathies (CMPs) require tailored investigation and management. A multidisciplinary team is essential to improve diagnosis and management of rare CMPs. A step-by-step clinical evaluation is required to reach aetiological diagnosis.